Development Of The Educational Game Math Land Using Construct 2 - Sinambela, Ilmi Suciani; Febri, Indah (Gameology and Multimedia Expert, 2025)
In the digital era, technological advancements have brought significant changes to In the digital era, technological advancements have brought significant changes to the field of education. Conventional learning methods often cause boredom among students, making it necessary to innovate the delivery of learning materials. One solution that can be implemented is the development of educational games, which combine entertainment and education to create an enjoyable learning experience for children. This study aims to develop an educational game that combines learning with play to facilitate a more effective and engaging learning process. The game development is carried out using the Construct 2 game engine, with the implementation of the ADDIE method (Analyze, Design, Development, Implementation, Evaluation) as a systematic framework to ensure the quality and effectiveness of the resulting educational games